Gummy Smile Correction with Diode Laser: Two Case Reports - Narayanan, Mahesh (J Int Oral Health, 2015)
Beautification of smiles is becoming an everyday requirement in dental practice. Apart from teeth, gingiva also plays an important role in smile esthetics. Excessive visualization of gingiva is a common complaint among patients seeking esthetic treatment. A wide variety of procedures are available for correction of excessive gum display based on the cause of the condition. Soft tissue diode laser contouring of gingiva is a common procedure that can be undertaken in a routine dental setting with excellent patient satisfaction and minimal post-operative sequale. Two cases of esthetic crown lengthening with diode laser 810 nm are presented here.